Strategic vaccination of hair sheep against Haemonchus contortus - Teixeira, Marcel (2019)
In this study, we evaluated in two trials a protocol designed to protect hair sheep using Barbervax®, a vaccine containing Haemonchus contortus gut membrane glycoprotein antigens. Results indicated that naturally infected vaccinated sheep had significant egg count reductions (90.2 ± 4.03%) compared with controls, although blood parameters remained relatively unchanged probably because the level of challenge was low. Vaccination prevented the periparturient rise in egg shedding of ewes, as well as egg shedding in lambs (37.1%). In the second trial, sheep which were experimentally exposed to higher artificial challenge also showed an efficient response to the vaccine as confirmed by high antibody levels and reduced egg counts and worm burdens (87 ± 5.4% and 79%) respectively. Thus, we believe that the vaccine should be integrated with other management practices for meat hair sheep as it has the advantages of adequate efficacy, reducing anthelmintic utilization and avoiding milk and environmental contamination with chemical residues.